Factors affecting academic failure in medical students in Iran - Zohreh Tajabadi; Matineh Sadat Miri; Soliman Ahmadi; Matineh Pourrahimi; Mojtaba Abdi; Hadi Jalilvand; Mohammad Helichi; Nadia Pirzade Moghaddam; Nafise Alinejade; Alireza Hazbenejad (Tabriz University of Medical Sciences, 2021)
Background: Students are considered part of the capital of each country. Several factors can affect their educational status and, as a result, contribute to their academic failure. The current study seeks to investigate the relationship between students' academic failure and the affecting factors with the Iranian Educational Ranking of Universities. Methods: This is a descriptive cross-sectional study. The required sample size was calculated using Cochran's formula. A researcher-made questionnaire with 5 parts was used to collect data. Kruskal Wallis and Spearman's analysis of variance was used for analysis. The significance level was considered as 0.05. Results: A total of 1215 people participated; 13.7% of students had had an academic failure and 2.0% of them were on academic probation. There was a correlation between university RAD rank and academic failure (r = -0.098 and P = 0.0001) as well as student satisfaction (r = 0.264 - P = 0.0001). There was a significant difference between an academic drop and academic grade in three ranks of university (Pv= 0.0001), and, interestingly, having moved from Rank 1 to 3, having academic grade increases, and having academic failure decreases. Conclusion: According to the findings of this study, the higher ranked the college campus is on the RAD scale, the higher the academic failure rate. For annual assessment of universities, it is proposed that assessment of academic failure and grades be used as a benchmark.